Analisis Dampak Stres Kerja dan Lingkungan Kerja terhadap Kinerja Guru dengan Kepuasan Kerja sebagai Mediator pada SDN di Kecamatan Cikarang Timur - Warsidi, Warsidi; Levianto, Jubei (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
This study adopts a quantitative approach with the aim of identifying and examining the influence of work stress and work environment on the performance of educators, with job satisfaction acting as a mediating variable. The research subjects consist of civil servant teachers (PNS) from 10 public elementary schools (SDN) in the East Cikarang District, totaling 58 individuals. Data analysis was conducted using the Structural Equation Modeling (SEM) method with a Partial Least Square (PLS) approach. The findings indicate that: (1) work stress has a positive and significant effect on teacher performance; (2) the work environment also has a positive and significant impact on performance; (3) job satisfaction contributes positively and significantly to the improvement of educators’ performance; (4) work stress affects performance indirectly through job satisfaction as a mediating variable; and (5) the work environment likewise influences performance indirectly via job satisfaction.